An Evaluation of the Effects of a Mild Delayed Verbal Punisher on Choice of an Immediate Reinforcer by Children With Autism. (September 2016) - Sy, Jolene R.; Green, Leonard; Gratz, Olivia; Ervin, Thea
Different combinations of immediate and delayed consequences differentially affect choice. Basic research has found that nonhuman animals are more likely to choose an alternative that produces an immediate reinforcer that is followed by a delayed punisher as the delay to punishment increases. The purpose of the current effort was to examine the choices of three individuals with autism when they were given the choice between receiving a larger amount of preferred food followed by a mild, delayed verbal punisher and a smaller amount of the preferred food. A secondary purpose was to determine whether signal presence and duration would affect the efficacy of the punisher (i.e., whether children would be more likely to select the smaller reward that was not followed by a delayed punisher). Results were idiosyncratic across children and highlight the need to evaluate choice under multiple arrangements.